The Effect of Centrifugation Speed on the Characteristics of Bromelin Enzyme Crude Extract from Flesh, Core and Peel Sipahutar Pineapple - Purba , Hendri F P; Sinaga , Hotnida; Husin , Amir (Journal of Environmental and Development Studies, 2024)
Bromelain enzymes can be utilized as a food supplement and pharmacy manufacturer. Pineapple is a natural source of bromelain enzymes. The centrifugation process is an extraction process to produce a crude extract of enzyme. Wasted parts of the Sipahutar pineapple plant have never been processed into bromelain enzyme. This research was aimed to determine the crude extract characteristics of the Sipahutar pineapple bromelain enzyme extracted with three centrifugation speeds. The research was conducted at the Food Analysis and Biochemistry Laboratory, University of North Sumatra from January to March 2023. The research was arranged in a completely randomized factorial design. The first factor is the part of the fruit used (B), namely the skin, flesh, and core, while the second factor is the centrifugation speed (K) which consists of 3000, 4000 and 5000 rpm. The study results showed that only the part of the fruit used (B) factor that affected the test parameters, especially pH and bromelain enzyme activity. The skin produced the highest pH (4.55) and enzyme activity (0.0035 U/ml) while the flesh produced the lowest pH (4,25), enzyme activity (0.0019 U/ml), and the highest soluble protein content (0.69 Âµg/ml).